Thresholds in Flux—the Standard for Ascertaining the Requirement of Organization for Armed Groups under International Humanitarian Law. (22nd December 2020) - Arai-Takahashi, Yutaka
Abstract: The requirement of organization is supposed to be of special importance in international humanitarian law (IHL). In the situation of international armed conflict (IAC), this requirement is implicit as part of the collective conditions to be fulfilled by irregular/independent armed groups to enable their members to claim the prisoners of war status under Article 4 A(2) of the Third Geneva Convention. In a non-international armed conflict (NIAC), the eponymous requirement serves, alongside the requirement of intensity of violence, as the threshold condition for ascertaining the onset of a NIAC. While the requirement of organization has not caused much of disputes in IACs, the international criminal tribunals have shown a willingness to examine scrupulously if armed groups in NIACs are sufficiently organized. Still, this article argues that there is need for a nuanced assessment of the organizational level of an armed group in some specific phases of the ongoing armed conflict whose legal character switches (from an NIAC to an IAC, vice-versa, and from a NIAC to a law-enforcement model). It explores what rationales and argumentative model may be adduced to explain such varying standards for organization in different contexts.